The Effects Of Angiotensin Iconverting Enzyme (ACE) I/D And Alphaactinin- 3 (ACTN3) R/X Gene Polymorphisms On Human Physical Performance And Health Within Malaysian Population - Yusof @ Hanafi, Hazwani Ahmad (2016)
A disparity population data set in the current literature with limited reports among Asian samples, coupled with the inconsistent findings among different ethnic groups, and lack of information for the involvement of angiotensin I-converting enzyme (ACE) I/D and alpha-actinin-3 (ACTN3) R/X gene polymorphisms in training adaptation have limited the ability of researchers to draw meaningful conclusions pertaining to the effects of these polymorphisms on human physical performance and health. Therefore, this doctoral research implemented three series of studies to examine the effects of ACE I/D and ACTN3 R/X gene polymorphisms on human physical performance and health within the Malaysian population.